Silylated oligomeric poly(ether-azomethine)s from monomers containing biphenyl moieties: synthesis and characterization. Issue 3 (2nd January 2018) - Tundidor-Camba, Alain; González-Henríquez, Carmen M.; Sarabia-Vallejos, Mauricio A.; Tagle, Luis H.; Hauyón, René A.; Sobarzo, Patricio A.; González, Alexis; Ortiz, Pablo A.; Maya, Eva M.; Terraza, Claudio A.
Abstract : In this study, four new silicon-containing poly(ether-azomethine)s with linear structures were prepared using original silicon and biphenyl moiety-containing monomers: two diamines and two dialdehydes. Abstract : In this study, four new silicon-containing poly(ether-azomethine)s with linear structures were prepared using original silicon and biphenyl moiety-containing monomers: two diamines and two dialdehydes. The oligomeric natures of the samples were established by GPC analysis, which showed chains containing 3 to 5 repetitive units. The monomers and the oligomeric samples were structurally characterized by NMR and FT-IR spectroscopy. The solubilities of the samples in common organic solvents and their thermal behavior enable improvement of their industrial and technological processability. The optical band gaps of the oligomeric samples were estimated from optical measurements (UV-vis), and their electrical behavior in films was determined using the four-point method. The surface arrangements and morphological characteristics of the films were determined via atomic force microscopy measurements. The roughness, area increase percentage and layer stiffness of the films were also measured using this technique.